Utiliza????o de estrat??gias metagen??micas para aplica????es biotecnol??gicas no setor de biocombust??veis - Bergmann, Jessica Carvalho (2013)
The necessity to be a self-suficient producer of fuels is stimulating research for alternative types of energy. Brazil, as well as other countries, is investing in this sector and in 2012 was the second largest biofuel producer in the world. Bioethanol production can double productivity with second generation technology in which bioethanol is produced from cellulose. Biodiesel production from oils using different feedstocks can also contribute for this independency in biofuels production, both locally and globally. This doctorate thesis is divided in two chapters, both attempting to make a contribution to the development of the biofuels sector in Brazil. The first chapter focuses on enzyme discovery for ethanol production from cellulose. The second chapter focuses on the characterization of the soil microbiota associated with oil palm plants with fatal yellowing, which has hindered the development of a biodiesel industry based on palm oil. The first chapter describes prospection for hydrolytic enzymes to be used for biomass deconstruction in second generation bioethanol production. Enzymes were screened from an Amazon soil large insert metagenomic library (30-50 kb). The library containing approximately 213,000 clones was functionally screened, and 15 clones with cellulolytic activity and 16 clones resistant to hydroquinone were identified. The sequences of these 31 clones and an additional 65 other random clones were obtained and analysed using the IMG/MER pipeline. In silico analysis identified several coding regions (CDS) that were amplified by PCR and cloned in expression vectors. The sequences for two beta-glucosidases enzymes, BGL17 and BGL18, were codon optimized before being expressed and purified. Characterization of both enzymes showed that the optimum temperature for BGL17 and BGL18 was 45oC and 40oC, respectively. The optimum pH for BGL17 and BGL18 was 6.0 and for 6.5, respectively. Half-life stability was approximately one hour for both enzymes. Regarding enzyme kinetics, BGL18 showed higher Vmax and Km (11 U/mg ?? 0.0011 and 0.36 mM ?? 0.01612) when compared to BGL17 (85 U/mg ?? 0.0028 and 0.30 mM ?? 0.017). Kcat was only calculated for BGL17 as 38.57 s-1 ?? 0.37 as the purification of BGL18 was not successfull. Chapter two aimed to study the soil bacterial diversity from oil palm trees affected by fatal yellowing disease (bud rot) in three different stages. The strategy used was pyrosequencing of the gene for the 16S ribosomal RNA (16S rRNA). Oil palm is an oilcrop produced in the north region of Brazil with hight oil yield, which makes it a good candidate for biodiesel production. However, oil palm trees are being affected by fatal yellowing (FY) for more than 20 years, but to this date no etiological agent was identified. Observation was reported where healthy palm tree were planted in the same spot as previously sick tree, developed FY after a period of time, suggesting that the disease could be transmitted by some microorganism in the soil. In this work, the gene for 16S rRNA was amplified from DNA extracted from soil of diseased oil palm trees (stages 5 and 8) and from plants with no symptoms of the disease and sequenced. Pyrosequencing originated 839,694 sequences. After artifacts and chimeras were removed, 498,397 sequences distributed in 9 samples (3 for each disease stage) remained to be analyzed. Sequences were analyzed using the Qiime pipeline (Quantitative Insights in Microbial Ecology) and taxonomic classification of sequences was obtained based on the RDP (Ribossomal Database Project). The most abundant phyla in the samples were Acidobacteria, Proteobacteria, Planctomycetes, Firmicutes and Verrucomicrobia. Alpha and Beta diversity were calculated and taxonomic comparisons were performed by STAMP software. Results showed that the bacterial communtiy associated with soils of diseaded plants on stage 5 (DCA5) and stage 8 had a higher number of observed OTUs than stage 0, as determined by the Chao1 phylogenetic diversity index. Beta-diversity analysis showed that the different biological replicates of soil from diseased plants of the same stage are significantly different, as shown in PCoA (Principal Coordenate Analysis). Taxonomic comparison showed more rare phyla associated to stages 5 and 8 of the disease. This work is the first to study the bacterial microbiota associated with soils of oil palm plants with and without symptoms of fatal yellowing with next generation sequencing.